Effect of Firm Size, Financial Distress and Debt Level on Hedging Decision on Manufacturing Companies Listed on IDX In 2016-2019 - Widyarti, Endang Tri; Witiastuti, Rini Setyo; Triyani, Dian (Universitas Negeri Semarang, 2021)
Supporting is an activity that can be taken by the company to play down the trade rate chance confronted. The reason of this inquire about is to decide the impact of firm estimate, monetary trouble and obligation level on supporting choices on fabricating companies recorded on IDX in 2016-2019. The sampling method of this study is purposive sampling and obtained 32 samples that meet the criteria of 105 companies that become observation data. Technical analysis used in this study is the analysis of logistic regression. And the testing getting results Firm Size, Financial Distress, Debt Level has no effect on hedging decisions.